diversidade.ID: citizen science project to help the observation of insects - Abrunhosa, João Carlos Costa (2020)
The citizen involvement in nature observation is being promoted by several biodiversity iniatives. Beyond the citizen engagement, there is sometimes the benefit of distributed data collection, by offering tools that can be used in mobile devices for capturing and document observations. Entomology is one of those fields in which the use of self-reported observations by curious and nature-lovers can help monitoring the populations of insects, especially in specific ecossystems, like the Baixo Vouga Lagunar in Aveiro. In this work, we propose a mobile app (diversidade.ID) that enables any citizen to report the observation of insects. The sighting is expected to be supplemented with photos and location data, acquired with the mobile phone. The distributed observations are aggregated for posterior review by collaborators, using a backoffice worklists management system. After classification, observations and shared in the platform for general access and exploration. The diversidade.ID application is available for the Android system and has been used in exploratory mode from students.